Coronary microvascular dysfunction is associated with exertional haemodynamic abnormalities in patients with heart failure with preserved ejection fraction. (7th October 2020) - Ahmad, Ali; Corban, Michel T.; Toya, Takumi; Verbrugge, Frederik H.; Sara, Jaskanwal D.; Lerman, Lilach O.; Borlaug, Barry A.; Lerman, Amir
Abstract : Aims: This study uniquely explored the relationship between coronary microvascular function and exercise haemodynamics using concurrent invasive testing. Methods and results: Fifty‐one consecutive patients with unexplained cardiac exertion symptoms, non‐obstructive coronary artery disease and normal left ventricular ejection fraction (>50%) underwent haemodynamic exercise assessment and concurrent coronary reactivity testing. Heart failure with preserved ejection fraction (HFpEF) was defined as a pulmonary arterial wedge pressure (PAWP) ≥15 mmHg at rest and/or ≥25 mmHg at peak exercise. Endothelium‐independent coronary microvascular dysfunction (CMD) was defined as a coronary flow reserve (CFR) ≤2.5, while endothelium‐dependent CMD was defined as ≤50% increase in coronary blood flow (CBF) in response to intracoronary acetylcholine infusions. Patients with HFpEF ( n  = 22) had significantly lower CFR (2.5 ± 0.6 vs. 3.2 ± 0.7; P  = 0.0003) and median %CBF increase in response to intracoronary acetylcholine [1 (−35; 34) vs. 64 (−4; 133); P  = 0.002] compared to patients without HFpEF ( n  = 29). PAWP was significantly higher in patients with endothelium‐independent CMD compared to controls during both rest and exercise. This significant elevation was only present during exercise in patients with endothelium‐dependent CMD compared to controls. CFR had significant inverse correlations with PAWP at rest (r = −0.31; P  = 0.03) and peak exercise (r = −0.47, P  = 0.001). CFR also had positive correlations with maximal exercise capacity (in W/kg) (r = 0.33, P  = 0.02). Conclusions: Coronary microvascular function is inversely associated with filling pressures, particularly during exercise. Both types of CMD are associated with higher filling pressures at peak exercise. These findings underscore the potential mechanism and therapeutic target for CMD and HFpEF. Abstract : Abnormal endothelium‐independent function and endothelium‐dependent function in patients with HFpEF. Patients with HFpEF exhibit an attenuated response to adenosine as well decreased blood flow in response to acetylcholine, reflecting abnormal coronary endothelium‐independent and endothelium‐dependent function, as compared to non‐HFpEF patients.